Lokaśāhī samājavāda : parisãvāda - Rājaguru, Vināyaka (Neharū Sāmājikaśāstra Vidyāsthāna Padvyuttara Vibhāga, Ṭiḷaka Mahārāshṭra Vidyāpīṭha, 1975)
Articles on various aspects of democratic socialism in the context of the Indian experience.